EVALUASI KOROSI BAJA KARBON RENDAH ASTM A36 PADA LINGKUNGAN ATMOSFERIK DI KABUPATEN JEMBER - Sumarji Sumarji (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2012)
Atmospheric corrosion is corrosion or degradation of materials in the atmosphere that occurs naturally. The corrosion rate varies for different materials and is influenced by several environmental factors, such as: humidity, temperature, and pollutant (NOx, SOx, Cl-, CO2). This research studies the corrosion rate of low carbon steel ASTM A36 in kabupaten Jember environment with different area. The location of research was done in the side of beach (Watu Ulo), the centre of city (Gajah Mada street) and the mountain range (Rembangan). The dimension of test racks and specimens for atmospheric exposure were prepared in accordance with the ASTM G 50 – 76. The cleaning of all corrosion products were done in accordance with the ASTM G 1- 90. The result shows that the highest corrosion rate is in the Watu Ulo as big as 2,82 mpy, than Gajah Mada street as big as 0,919 mpy. The lowest corrosion rate is in Rembangan as big as 0,844 mpy. From the micro photographs, it is found that low carbon steel ASTM A36 corrode by uniform and pitting formation. Keywords: atmospheric corrosion, uniform, pitting